PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA PT. BANK RAKYAT INDONESIA (PERSERO) Tbk. - Samsul Rizal; Vivid Violin; Eka Wardiana; Irwan Abdullah (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
The purpose of this study was to determine the effect of service quality on customer satisfaction at PT. Bank Rakyat Indonesia (Persero) Tbk. Unit Bengo Branch Watampone. This research was conducted at PT. Bank Rakyat Indonesia (Persero) Tbk. Unit Bengo Branch Watampone, the research population is all customers of PT. Bank Rakyat Indonesia (Persero) Tbk. Unit Bengo Branch Watampone Unit, which was met at the time of the research, where the population was 500 customers while the sample size was determined using incidental sampling technique, which was 84 respondents. Data collection uses descriptive statistical techniques, simple linear regression analysis, and hypothesis testing. The results of data analysis obtained t count of 7.669 while t table amounted to 1.98932, so the t test hypothesis variable service quality has a positive effect on customer satisfaction. From the calculation of SPSS obtained R = 0.646, with R2 = 0.418 or 41.8%, the amount of customer satisfaction has been explained in the service quality data. While the rest, which is 0.582 or 58.2%, information about the amount of customer satisfaction cannot be explained by these independent variables.